Dl-3-n-Butylphthalide Alleviates Demyelination and Improves Cognitive Function by Promoting Mitochondrial Dynamics in White Matter Lesions - Feng, Yiwei; Guo, Min; Zhao, Hongchen; Han, Sida; Hao, Yining; Yuan, Yiwen; Shen, Weiwei; Sun, Jian; Dong, Qiang; Cui, Mei (Frontiers in Aging Neuroscience, 2021)
White matter lesions (WMLs) are a type of cerebrovascular disorder accompanied by demyelination and cognitive decline. Dl-3-n-butylphthalide (D1-NBP) is a neuroprotective drug used for the treatment of ischemic cerebrovascular diseases, although the function of DI-NBP on WML is still not clear. This study aims to investigate whether DI-NBP affects cognitive function and ameliorates demyelination in a model of WML. The bilateral carotid artery stenosis (BCAS) mouse model and in vitro brain slice cultures with low glucose and low oxygen (LGLO) treatment were adopted. The Dl-NBP was administered intragastrically for 28 days after BCAS or added at a dose of 50 μm for 48 h after LGLO. Spatial learning and memory were evaluated by an eight-arm radial maze. Demyelination was detected using a TEM. Mitochondrial dynamics were assessed by time-lapse imaging in the cultured brain slices. The function of the synapse was evaluated by the patch clamp technique. In BCAS mice, obvious demyelination and cognitive decline were observed, while both were significantly relieved by a high-dose D1-NBP treatment (100 mg/kg). Along with demyelination, mitochondrial accumulation in the axons was significantly increased in the BCAS mice model, but with the treatment of a high-dose D1-NBP, mitochondrial accumulation was mitigated, and the anterograde/retrograde transport of mitochondria was increased. Following the improved anterograde/retrograde transport of mitochondria, the synapse activity was significantly upregulated while the reactive oxygen species (ROS) generation was remarkably decreased in the cultured brain slices. In addition, we identified syntaphilin (SNPH) as the downstream target of D1-NBP. The overexpression of SNPH mediated the effects of D1-NBP in mitigating axonal mitochondrial accumulation. In conclusion, the D1-NBP treatment significantly relieved demyelination and improved spatial learning and memory in the WML model by promoting mitochondrial dynamics. These neuroprotective effects of D1-NBP were mediated by inhibiting the mitochondrial arching protein, SNPH, which provided a potential therapeutic target for WML.